Polysomy is associated with poor outcome in 1p/19q codeleted oligodendroglial tumors. Issue 9 (29th May 2019) - Chen, Hui; Thomas, Cheddhi; Munoz, Felipe Andres; Alexandrescu, Sanda; Horbinski, Craig M; Olar, Adriana; McGuone, Declan; Camelo-Piragua, Sandra; Wang, Lu; Pentsova, Elena; Phillips, Joanna; Aldape, Kenneth; et al.
Abstract: Background: Chromosomal instability is associated with earlier progression in isocitrate dehydrogenase (IDH)–mutated astrocytomas. Here we evaluated the prognostic significance of polysomy in gliomas tested for 1p/19q status. Methods: We analyzed 412 histologic oligodendroglial tumors with use of 1p/19q testing at 8 institutions from 1996 to 2013; fluorescence in situ hybridization (FISH) for 1p/19q was performed. Polysomy was defined as more than two 1q and 19p signals in cells. Tumors were divided into groups on the basis of their 1p/19q status and polysomy and were compared for progression-free survival (PFS) and overall survival (OS). Results: In our cohort, 333 tumors (81%) had 1p/19q loss; of these, 195 (59%) had concurrent polysomy and 138 (41%) lacked polysomy, 79 (19%) had 1p/19q maintenance; of these, 30 (38%) had concurrent polysomy and 49 (62%) lacked polysomy. In agreement with prior studies, the group with 1p/19q loss had significantly better PFS and OS than did the group with 1p/19q maintenance ( P < 0.0001 each). Patients with 1p/19q loss and polysomy showed significantly shorter PFS survival than patients with 1p/19q codeletion only ( P < 0.0001), but longer PFS and OS than patients with 1p/19q maintenance ( P < 0.01 and P < 0.0001). There was no difference in survival between tumors with >30% polysomic cells and those with <30% polysomic cells. Polysomy had no prognostic significance on PFS or OS in patients with 1p/19q maintenance. Conclusions: The presence of polysomy in oligodendroglial tumors with codeletion of 1p/19q predicts early recurrence and short survival in patients with 1p/19q codeleted tumors.